2022
DOI: 10.1001/jama.2022.2896
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Transthyretin Val122Ile Variant With Incident Heart Failure Among Black Individuals

Abstract: Key PointsQuestionsWhat is the association between amyloidogenic TTR gene variation (Val122Ile) and the risk of heart failure?FindingsIn this retrospective cohort study that included 7514 Black participants in the US with a median 11.1 years of follow-up, the incidence of heart failure was 15.6 per 1000 person-years among Val122Ile variant carriers compared with 7.2 per 1000 person-years among noncarriers, with an adjusted hazard ratio of 2.43.MeaningBeing a carrier of the Val122Ile variant was significantly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…Behavior, cognition, neuropeptide amidation, neurogenesis, nerve regeneration, and axonal growth are some of the cellular processes where TTR has an important role (Vieira and Saraiva 2014 ). Further, mutations in the TTR gene are implicated in the etiology of several diseases, including amyloidotic polyneuropathy, euthyroid hyperthyroxinaemia, amyloidotic vitreous opacities, cardiomyopathy, oculoleptomeningeal amyloidosis, meningocerebrovascular amyloidosis, and carpal tunnel syndrome (Bekircan-Kurt et al 2022 ; Coniglio et al 2022 ; Parcha et al 2022 ; Takahashi et al 2022 ; Yee et al 2019 ). Besides, maternal exposure to PFASs can result in serum concentration of PFASs in fetuses and newborns, which leads to hypothyroidism, slow growth and development, and mental retardation as explained in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Behavior, cognition, neuropeptide amidation, neurogenesis, nerve regeneration, and axonal growth are some of the cellular processes where TTR has an important role (Vieira and Saraiva 2014 ). Further, mutations in the TTR gene are implicated in the etiology of several diseases, including amyloidotic polyneuropathy, euthyroid hyperthyroxinaemia, amyloidotic vitreous opacities, cardiomyopathy, oculoleptomeningeal amyloidosis, meningocerebrovascular amyloidosis, and carpal tunnel syndrome (Bekircan-Kurt et al 2022 ; Coniglio et al 2022 ; Parcha et al 2022 ; Takahashi et al 2022 ; Yee et al 2019 ). Besides, maternal exposure to PFASs can result in serum concentration of PFASs in fetuses and newborns, which leads to hypothyroidism, slow growth and development, and mental retardation as explained in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the Original Investigation titled “Association of Transthyretin Val122Ile Variant With Incident Heart Failure Among Black Individuals,” published in the April 12, 2022, issue of JAMA , an author name was misspelled. In the byline, the third author, “Marguerite R. Ivin, PhD” should have been “Marguerite R. Irvin, PhD.” This article was corrected online.…”
mentioning
confidence: 86%
“…In this issue of JAMA , Parcha et al add to the growing literature on the risk of heart failure associated with the TTR Val122Ile mutation, the genetic basis of hereditary transthyretin amyloidosis cardiomyopathy (hATTR-CM). This report on the outcomes associated with heritable, amyloid-related heart failure is particularly timely.…”
mentioning
confidence: 99%
“…Parcha et al sought to quantify the association of the TTR Val122Ile variant with incident heart failure and mortality in the Reasons for Geographic and Racial Differences in Stroke (REGARDS) study, which includes a large, geographically diverse cohort of Black individuals. The investigators analyzed data from 7514 self-identified Black participants who had genetic data available and no evidence of heart failure at baseline.…”
mentioning
confidence: 99%
See 1 more Smart Citation